AUDIT QUALITY, AUDIT COMMITTEE, AND EARNINGS MANAGEMENT PRE-POST IFRS IMPLEMENTATION: EVIDENCE FROM INDONESIAN CONSUMER GOODS COMPANIES - Puspita, Adya; Setiawan, Doddy (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2025)
The purpose of this study is to examine the association of audit quality and audit committee on earnings management through the time line of IFRS implementation phases. The sample of this study consists of consumer goods companies with 237 firm-years observations during 2008 – 2018 from the Indonesian Stock Exchange. This study shows that audit quality can diminish accrual earnings management rather than in real earnings management. Audit committee works well on accrual earnings management rather than on real earnings management. This study limited to Indonesian Consumer Goods companies only. Future researchers might expand the sample and consider qualitative methods to provide valuable insights the minds of the managers and stakeholders, and explanations regarding manager’s incentives can be obtained.